PENGARUH KOMITE-KOMITE PENUNJANG DEWAN KOMISARIS TERHADAP TAX PLANNING DENGAN STRUKTUR KEPEMILIKAN KELUARGA SEBAGAI VARIABEL PEMODERASI (STUDI EMPIRIS PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011-2015) - MUHAMMAD SYAFIQURRAHMAN; SRI SURANTA (Universitas Sarjanawiyata Tamansiswa, 2020)
This study aims to determine the influence of committees under the board of commisioners towards tax planning using the structure of family ownership as the moderating variable. Committees under the board of commisioners included in this study are an audit committess, nomination committess or remuneration, risk policy committee, as well as corporate governance policy committee entirely proxied by the size of the committee. The dependet variable, tax planning, is proxied by Tax Retention Rate (TRR); while moderating variables, the ownership structure, was determined by the ratio of family ownership. This study use profitability as control variable and moderating regression analysis is employed to analyzed the data. The sample used 230 manufacture companies listed on the Stock Exchange Year 2011-2015 and used purposive sampling as sampling method. The result in this study are structure of family ownership has no effect on the relationship between the audit committees and profitability toward tax planning, structure of family ownership has positive effect on the relationship between the nomination committess or remuneration toward tax planning, and then structure of family ownership has negative effect on the relationship between the risk policy committee and corporate governance policy toward tax planning